Wear behavior at high temperature of ZrO2–Y2O3 (YSZ) plasma‐sprayed coatings (2024)
ABSTRACT:The wear behavior of two plasma-sprayed zirconia–ytria coatings was studied at high temperatures. Agglomerated and sintered, as well as fused and crushed zirconia–ytria feedstock powders were used to manufacture bimodal and monomodal coatings by atmospheric plasma spraying onto an INCONEL 718 substrate previously coated with a NiCrAlY bond coat. The structure of the coatings was analyzed by SEM on their cross section and surface. The samples were subjected to wear conditions by sliding contact through a ball-on-disk test up to 1000 °C, using an alumina ball 6 mm in diameter as the counterbody, on which a load of 5 N was applied. The samples were rotated during 20000 cycles, reaching a speed of 0.10 m·s−1 at the contact area with the counterbody. The porosity, phase, and mechanical properties were determined before and after wear tests. The results indicate that at 25 °C, both coatings have enough mechanical resistance to with stand the tribological conditions they were exposed to. Therefore, low wear rates were produced by ductile deformation. The tribological conditions became more aggressive as the thermal stresses increased with the test temperature, producing cracking, and detaching particles in the coatings tested at 500 and 750 °C. Consequently, high wear rates related to britle deformation were obtained. However, the transformation of the amorphous phase to the t′-zirconia phase, produced at 1000 °C, increased the hardness of both coatings and, consequently, their wear resistance; thus, the predominant mechanism of damage was ductile deformation, with wear rates similar to those obtained when the coatings were tested at 25°C.